Assessing the role of fluctuating renewables in energy transition: Methodologies and tools. (15th May 2022) - Bompard, Ettore; Ciocia, Alessandro; Grosso, Daniele; Huang, Tao; Spertino, Filippo; Jafari, Mehdi; Botterud, Audun
Highlights: Electricity, the most direct and effective use of RES, is in center of energy transition. An interdisciplinary procedure suitable for the planning of RES is presented. Key points and procedures for the assessment of large-scale RES installation is presented. Simulation on Eygiption case shows the technical and economical viability. Abstract: Due to the environmental impacts brought by current energy schemes, the energy transition, a new paradigm shift from fossil fuels to renewable energy, has been widely accepted and is being realized through collective international, regional, and local efforts. Electricity, as the most direct and effective use of renewable energy sources (RES), plays a key role in the energy transition. In this paper, we first discuss a viable pathway to energy transition through the electricity triangle, highlighting the role of RES in electricity generation. Further, we propose methodologies for the planning of wind and solar PV, as well as how to address their uncertainty in generation expansion problems. Finally, by using a web-based tool, "RES-PLAT" 1, we demonstrate the scheme in a case study in Egypt, which evaluates the impacts and benefits of a large-scale RES expansion. 2